VD_FINDINFO HC / 2021 / 142 vom 7. April 2021 - VD Tribunal cantonal (2021)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, REJET DE LA DEMANDE, INDEMNITÉ ÉQUITABLE | 337 CO, 337c al. 3 CO, 308 al. 1 let. a CPC (CH), 311 al. 1 CPC (CH)